2021
DOI: 10.1002/jmv.26761
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of SARS‐CoV‐2 RNA in nasopharyngeal samples from infected patients with mild disease

Abstract: Diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS‐COV‐2) cases is based on the count of real‐time reverse transcription‐plymerase chain reaction (RT‐PCR) positive people. Viral load by real‐time RT‐PCR has been suggested as a biomarker of the SARS‐CoV‐2 infection. However, the association of viral load and severity of the disease is not yet resolved. Nasopharyngeal samples from 458 patients were tested by RT‐PCR for SARS‐CoV‐2 diagnosis. Relative quantitation was made by the comparative thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Understanding the role of children in the transmission of the virus would help designing appropriate control measures, planning the reopening of schools and restoring intergenerational contacts 3 . Several studies have addressed the viral loads of children, some have concluded that viral loads are not higher than adults 1 , 4 but some of them found the opposite 5 , 6 . Yet determination of viral loads is complicated by the lack of standardization and the nature of nasopharyngeal samples that are taken by surface swabbing 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the role of children in the transmission of the virus would help designing appropriate control measures, planning the reopening of schools and restoring intergenerational contacts 3 . Several studies have addressed the viral loads of children, some have concluded that viral loads are not higher than adults 1 , 4 but some of them found the opposite 5 , 6 . Yet determination of viral loads is complicated by the lack of standardization and the nature of nasopharyngeal samples that are taken by surface swabbing 7 .…”
mentioning
confidence: 99%
“…Some studies use standard curves to translate Ct values into RNA copies/ml 1 , one used the weight of collected secretions to give RNA copies/g of secretion 4 but these approaches do not address the variation in the amount of sample collected by the swabs. An accurate normalization assay should be based on a marker of collected cell mass like the human RNAseP 6 , 7 .…”
mentioning
confidence: 99%
“…Since the early phase of this pandemic, RT-qPCR tests have been used for diagnoses, epidemiological studies, and political decision making [27][28][29]. Severe cases with high infectivity usually show high viral loads (i.e., low Ct values) and vice versa [30]. However, the interpretation of positive results needs extra caution because Ct values can vary due to differences in PCR conditions [31].…”
Section: Discussionmentioning
confidence: 99%
“…This study also suggests that older individuals over the age of 60 have prolonged infections (viral loads of 1.40-2.19 log 10 RNA cp/ test) up to 2 weeks post symptom onset, whilst children under 10 experienced peak viral loads (2.50 log RNA cp/ test) during the first 2 days following symptom onset declining rapidly thereafter. 133 Recent reports published by bodies such as the AACC (American Association for Clinical Chemistry) and PHE have outlined the challenges with using Ct values for estimating viral loads thereby clearly highlighting the need for quantitative molecular technologies for viral load monitoring, which would help to support both clinical and public health decisions. 113,114,129,133,134…”
Section: Analytical Methods Accepted Manuscriptmentioning
confidence: 99%
“…133 Recent reports published by bodies such as the AACC (American Association for Clinical Chemistry) and PHE have outlined the challenges with using Ct values for estimating viral loads thereby clearly highlighting the need for quantitative molecular technologies for viral load monitoring, which would help to support both clinical and public health decisions. 113,114,129,133,134…”
Section: Analytical Methods Accepted Manuscriptmentioning
confidence: 99%